Rancang Bangun Sistem Informasi Klinik Gigi Berbasis Web Menggunakan Metode Extreme Programming - Affandi Agung Laksono; Erni Rohyati Putri; Muchlas Syahlanisyiam; Saprudin (CV. Shofanah Media Berkah, 2023)
In the current era of globalization, information systems using highly sophisticated and modern computer technology will make it easier for us to perform data processing that can save time, space and costs. And the results of an information obtained will be very satisfying, useful and beneficial from an institution or agency that uses it. Processing data and information quickly, precisely and efficiently is an important thing needed for institutions or agencies, one of which is the Jayanti Dental Clinic. The process of finding patient data so far still uses the manual method, the scheduling system is ineffective, and on the other hand it is difficult for patients to find out whether the clinic is open or not because the clinic's operating hours are not certain every day, with this website technology it is hoped that it can help prospective patients to get clinical information that is far from the Jayanti dentist clinic. A good information system can help improve efficiency and productivity in the daily operations of a dental clinic. The Extreme Programming (XP) method is a software development methodology that involves practices such as adaptive planning, continuous testing, and iterative delivery. This research was conducted by applying XP principles in every stage of dental clinic information system development. The development stages include planning, needs analysis, design, implementation, testing, and delivery. During the development stage, the XP method was applied by carrying out adaptive planning, continuous testing, and iterative delivery to ensure the quality of the information system. The results of this study are dental clinic information systems that can improve efficiency and productivity in the daily operations of a dental clinic.